Формування інвестиційної привабливості молокопереробних підприємств - Сидоров, Іван Петрович; Sydorov, Ivan Petrovych (Дніпровський ДАЕУ, 2020)
Досліджено теоретико-методичні та практичні аспекти формування інвестиційної привабливості молокопереробних підприємств. Удосконалено понятійно-категоріальний апарат у частині уточнення сутності економічних категорій «інвестиції», «інвестиційна привабливість молокопереробного підприємства», «інвестиційний ризик». Встановлено, що основним концептуальним підходом до визначення інвестицій та управління інвестиційним розвитком підприємства є стратегічний підхід, який пов’язаним з визначенням мети та основних напрямків інвестування, створенням умов підвищення інвестиційної привабливості підприємства. Інвестиції слід розглядати як процеси вкладення капіталу й одержання результату вкладень, що є, у свою чергу, результатом експлуатації капіталу. Ці процеси нерозривні, взаємозалежні та взаємозумовлені. Водночас у діяльності підприємств інвестиційний процес розглядається як сукупність інвестиційних циклів, які відбуваються невпинно і здійснюються свідомо з метою як простого, так і розширеного відтворення капіталу підприємства з урахуванням стану мікро- і макрооточення його діяльності. Поняття «інвестиційна привабливість підприємства» запропоновано розглядати як багаторівневу інтегральну характеристику підприємства як об’єкта доцільності інвестування у його розвиток власних коштів та інвестиційних ресурсів стратегічних або фінансових інвесторів з урахуванням сукупності факторів екзогенного та ендогенного впливу за прийнятного рівня ризику вкладення інвестицій. Інвестиційна привабливість підприємства є складовою його загальної економічної стратегії розвитку і передбачає ефективне застосування різноманітних форм інвестування з метою забезпечення високої ринкової вартості підприємства та сталих темпів розвитку. При визначенні об’єктів інвестування кожен інвестор ставить перед собою певну мету. Стратегічні та фінансові інвестори розглядають інвестиційну привабливість підприємства по-різному, вкладаючи у цю категорію різне змістовне наповнення залежно від їх пріоритетних цілей. Результати досліджень дозволяють виокремити чотири класифікаційні групи системоутворюючих складових інвестиційної привабливості підприємства, а саме: інвестиційна привабливість підприємства як умова його розвитку; інвестиційна привабливість підприємства як необхідна умова для інвестування; інвестиційна привабливість як інтегрована сукупність показників функціонування підприємств; інвестиційна привабливість підприємства як показник ефективності використання інвестицій. Теоретично доведено, що на інвестиційну привабливість підприємств впливає низка факторів, серед яких необхідно узагальнити політичні, економічні, соціальні та технологічні фактори. Ідентифіковано основні проблеми, які перешкоджають залученню інвестицій у розвиток підприємств молокопереробної галузі. У вітчизняному молочному бізнесі спостерігається тенденція концентрації виробництва, витіснення дрібних молокозаводів з ринку, поглинання їх великими компаніями та посилення трьохрівневої конкуренції між молокопереробними підприємствами. Відстежується закономірність збільшення залучення кредитних ресурсів у інвестиційну діяльність молокопереробних підприємств при зменшенні прибутковості їх виробничої діяльності. Здійснено оцінку впливу факторів на формування інвестиційної привабливості молокопереробних підприємств. За результатами практичного застосування пропонованої комплексної методики оцінювання інвестиційної привабливості молокопереробних встановлено, що дефіцит коштів у більшості молокопереробних підприємств не дає змоги вчасно розрахуватися за своїми невідкладними фінансовими зобов’язаннями та формує високий рівень кредиторської заборгованості. Зокрема, МПП1 має найвищий рівень віддачі основного капіталу, оборотності обігових коштів, обсягів реалізації молокопродукції та рентабельності її продажу. МПП2 в достатній мірі забезпечене економічними ресурсами, що дозволяє застосовувати інноваційні технології виробництва молочної продукції. Часткові показники інвестиційної привабливості МПП3 близькі до нижньої межі допустимої інвестиційної привабливості, а показники ділової активності та ліквідності й платоспроможності перевищують нормативні значення. Незважаючи на те, що на МПП5 спостерігається ріст обсягів реалізації молочної продукції, рівень його інвестиційної привабливості є низьким, причому за деякими показниками близьким до гранично допустимої межі нормативних значень. Значення показника інвестиційної привабливості МПП4 значно вийшло за межі гранично припустимого рівня. Значну частку в структурі власного капіталу підприємств молокопереробної галузі становить інший додатковий капітал та нерозподілений прибуток. Збільшення частки власного капіталу призвело до зменшення позикових та залучених коштів. У структурі позикових та залучених коштів молокопереробної галузі найбільша частка припадає на поточні зобов’язання, серед яких кредиторська заборгованість становить 71,2 % у загальному складі поточних зобов’язань 2014 р., та 68,7 % – 2018 р. При цьому немає чіткої залежності зміни обсягів інвестиційних вкладень від обсягу прибутку. Навіть за умови збитковості досліджувані молокопереробні підприємства здійснювали капітальні інвестиції, що свідчить про їх важливість для господарської діяльності та формування інвестиційної привабливості підприємств галузі. Удосконалено методичний підхід до управління інвестиційною привабливістю молокопереробних підприємств з урахуванням їх вартісної оцінки. Аргументовано, що вибір і розробка інвестиційних проектів повинні базуватися на зростанні ринкової вартості бізнесу в довгостроковому періоді, яке забезпечується за рахунок результатів реалізації інвестиційних проектів, що створюють економічну додану вартість підприємства. Ключовим критерієм вартості будь-якого об’єкта власності є його інвестиційна привабливість. Інвестиційна привабливість для кожного суб’єкта економічних відносин є індивідуальною, якісно і кількісно визначена у часі, просторі й вартості. Проте як загальну інвестиційну привабливість об’єкта для власника можна виділити його здатність приносити дохід. Розроблений у дослідженні вартісний підхід до оцінки й управління інвестиційною привабливістю підприємства характеризується положеннями, які включають синтез статичної і динамічної теорії економічних явищ, єдність оцінки й управління вартістю підприємства та синтез економіки й менеджменту. Надано пропозиції щодо інвестиційного проектування у процесі формування інвестиційної привабливості молокопереробних підприємств. В дослідженні розроблено послідовність інвестиційних дій з реалізації будівництва цеху сухих молочних продуктів у ТОВ «Синельниківський молокозавод», що дасть можливість підвищити обсяги реалізації молочної продукції, його оціночну вартість та інвестиційну привабливість. Для збільшення грошових потоків та підвищення інвестиційної привабливості ТОВ «Інтер-мол» розроблено інвестиційний проект виробництва морозива з натуральної сировини. Оцінювання прибутковості інвестиційного проекту здійснено визначенням основних грошових потоків з урахуванням темпів нарощування виробництва. Найбільш практичним підходом урахування ризиків при оцінці інвестиційних проектів молокопереробних підприємств є методи розподілення ймовірності різних сценаріїв розвитку подій у майбутньому при обчисленні показників ризику. The theoretical, methodological and practical aspects of forming the investment attractiveness of dairy enterprises are investigated. Improved conceptual and categorical apparatus in terms of clarifying the essence of economic categories "investment", "investment attractiveness of dairy enterprises", "investment risk". It was established that the main conceptual approach to defining investments and managing the investment development of the enterprise is a strategic approach, which is related to defining the purpose and main directions of investing, creating conditions for increasing the investment attractiveness of the enterprise. Investments should considered as processes of capital investment and the result of investments, which in turn is the result of capital exploitation. These processes are inseparable, interdependent and interdependent. At the same time, in the activity of enterprises, the investment process is consider as a set of investment cycles that are continuous and carried out deliberately for the purpose of both simple and extended reproduction of the capital of the enterprise, taking into account the state of micro- and macro- environment of its activity. The term "investment attractiveness of enterprise" proposed multi seen as integral characteristics of the enterprise as an object advisability of investing in the development of its own funds and investment resources strategic or financial investors considering a combination of factors exogenous and endogenous influence the acceptable level of risk investment. The investment attractiveness of an enterprise is part of its overall economic development strategy and involves the effective use of various forms of investment in order to ensure the high market value of the enterprise and a steady pace of development. In determining the objects of investment, each investor has set itself a goal. Strategic and financial investors view the investment attractiveness of an enterprise differently, putting different content in this category depending on their priority goals. The research results allow to distinguish four groups of system components classification of investment attractiveness, namely the investment attractiveness of the enterprise as a condition of its development; the investment attractiveness of the enterprise as a necessary condition for investment; investment attractiveness as an integrated set of enterprise performance indicators; the investment attractiveness of the enterprise as an indicator of the efficiency of the use of investments. Theoretically proved that the investment attractiveness of enterprises affects a number of factors, including the need to generalize the political, economic, social and technological factors. Identified the main problems that hinder investment in the development of dairy industry enterprises. In the domestic dairy business trend of concentration of production, displacement of small dairy market, absorption of large companies and enhance the three-level competition among dairy processing enterprises. Tracks law increasing attraction of credit resources in milk business investment while reducing the profitability of their production activities. The influence of factors on the formation of investment attractiveness of dairy enterprises has been evaluated. Because of the practical application of the proposed comprehensive methodology for evaluating the investment attractiveness of dairies, it is establish that the shortage of funds in most dairies does not allow timely settlement of their urgent financial obligations and creates a high level of accounts payable. Dairy enterprise № 1 has the highest level of return on fixed capital, turnover of working capital, sales of milk products and profitability of its sale. Dairy enterprise № 2 is sufficiently provided with economic resources, which allows applying innovative technologies of dairy production. Partial indicators of investment attractiveness of Dairy enterprise № 3 are close to the lower limit of permissible investment attractiveness, and indicators of business activity, liquidity and solvency exceed regulatory values. Despite the fact that the Dairy enterprise № 5 observed growth in sales of dairy products, the level of investment attractiveness is low, and according to some figures close to the maximum allowable limits of normative values. The value of the investment attractiveness indicator of Dairy enterprise № 4 is well beyond the maximum permissible level. A significant share in the equity of companies dairy industry is another additional capital and retained earnings. An increase in the share of equity resulted in a decrease in borrowed and borrowed funds. In the structure of loans and borrowings of the dairy industry, current liabilities account for the largest share, of which payables accounted for 71.2% of the total current liabilities of 2014, and 68.7% for 2018. There is no clear change in volume depending on the amount of investments profit. Even under conditions of loss, the investigated dairy enterprises made capital investments, which testifies to their importance for economic activity and formation of investment attractiveness of the enterprises of the branch. Methodical approach to managing the investment attractiveness of dairy companies based on their valuation. Argued that the selection and development of investment projects should be based on the growth of the market value of the business in the long run, which is provided by the results of investment projects that create economic value added business. A key criterion for the value of any object property is its investment attractiveness. Investment attractiveness for each economic entity is individual, qualitatively and quantitatively defined in time, space and value. However, the overall investment attractiveness of the property to the owner can be distinguished by its ability to generate revenue. The higher investment attractiveness, the greater the value of the appraised value of dairy enterprises. Designed in valuable research approach to the assessment and management of investment attractiveness of enterprise is characterized provisions that include the synthesis of static and dynamic theory of economic phenomena, the unity of assessment and cost management company and the synthesis of economics and management. The management of the investment attractiveness of dairy enterprises is carried out on the basis of various financial, economic and organizational procedures, which include the assessment of the present value of the business, as well as the development and implementation of measures for the creation or acquisition of new elements of assets, reduction or expansion of production of certain types of dairy products. The result of such management is to maximize the value of the dairy enterprise that implements the investment project. The propositions for investment planning in the process of investment attractiveness of dairy enterprises. The study has developed a sequence of investment actions for the implementation of the construction of a shop for dried dairy products in “Sinelnikovsky Dairy” LLC, which will increase the volume of sales of dairy products, its estimated value and investment attractiveness. The proposed investment project is considered effective because the net present value of 1541.2 thousand UAH., the index of profitability of the project – 1.45. In order to increase cash flow and increase the investment attractiveness of “Inter-Mol” LLC, an investment project for the production of ice cream from natural raw materials was developed. Evaluation of profitability of the project made major determining cash flows considering increasing production rates. According to calculations proved the possibility of obtaining a satisfactory level of profitability, and therefore the feasibility and profitability of the project. The most practical approach in assessing the risk of investment projects milk enterprises are methods of distribution of probabilities of various scenarios in the future when calculating risk indicators.
Formation of investment attractiveness of dairy enterprises
Keywords: розвиток; rozvytok; вартісний підхід; vartisnyi pidkhid; інвестиції; investytsii; інвестиційна діяльність; investytsiina diialnist; інвестиційний ризик; investytsiinyi ryzyk; молокопереробне підприємство; molokopererobne pidpryiemstvo